A preliminary study of the appropriation of Van Helmont's oeuvre in Britain in chymistry, medicine and natural philosophy - Ducheyne, Steffen (Ambix, 2008)
Van Helmont's work was of major importance in seventeenth-century medicine, chymistry and natural philosophy. His work was a source of inspiration and mystery and an authoritas. His oeuvre was, together with that of many others, the culminating point of an ongoing process, starting in the Middle Ages, of turning medicine into a scientific discipline. In this essay, the appropriation, that is, the process of assimilation of an author's work by other scholars, of Van Helmont's oeuvre in England will be studied among chymists, physicians and natural philosophers (the distinctions between these three groups is primarily conceptual, but in practice hard to distinguish). Appropriation reminds us that the process of assimilating ideas of an author by contemporaries or later generations is not a passive activity, for scholars actively adapt and interpret them in new ways not initially envisaged by its original author.